Structure, energetics and bioactivity of silicon oxycarbide-based amorphous ceramics with highly connected networks. Issue 4 (April 2018) - Ionescu, Emanuel; Sen, Sabyasachi; Mera, Gabriela; Navrotsky, Alexandra
Abstract: Mg and Ca substituted silicon oxycarbides are investigated with respect to their network architecture, enthalpy of formation and bioactivity. The synthesized materials have highly connected structural network with an open architecture and a minor but critical fraction of depolymerized Q-species. This combination of structural features allows for providing bioactivity at the same time with enhanced thermo-mechanical robustness and crystallization resistance. It is argued that silicon oxycarbide amorphous ceramics may consequently serve as model compounds for developing rational design concepts for advanced bioactive glasses.